Dynamic Behavior of the Platform-Vibrator with Soft Impact. Part 3. Effect of Stiffness Parameters. Transient Chaos - Lizunov, P.P.; Pogorelova, O.S.; Postnikova, T.G. (Discontinuity, Nonlinearity, and Complexity, 2026)
Platform-vibrator with shock is widely used in the construction industry for compacting and molding large concrete products. Its mathematical model corresponds to a two-body 2-DOF vibro-impact system with a soft impact. A soft impact is simulated with nonlinear Hertzian contact force. The choice of stiffness parameters greatly affects the model dynamic behavior. Some of their changes make it possible to increase the compaction efficiency. But the same changes in the stiffness parameters can lead to the emergence of undesirable and even dangerous nonlinear phenomena, such as chaotic motion, interior crisis, crisis-induced intermittency, transient chaos, and a hysteresis zone with coexisting regimes obtained for different initial conditions. The identity of the observed modes was confirmed by several methods. A performed detailed analysis of the influence of the platform-vibrator stiffness parameters at its dynamic behavior may be useful in the design and operation of this equipment. It can help to avoid the unwanted behavior because to the wrong choice of system stiffness parameters. Numerous Figures and Tables clearly and convincingly demonstrate the results of numerical studies.